A tipping point in refreezing accelerates mass loss of Greenland’s glaciers and ice caps - B. Noël (Nature Portfolio, 2017)
Mass loss of Greenland’s glaciers and ice caps (GICs) is a major contributor to contemporary sea-level rise. Here, the authors identify the year 1997 as a tipping point in GICs mass loss induced by a rapid deterioration of the refreezing capacity of inland snow, resulting in irreversible long-term mass loss.